Cabo Verde, 30 anos de independência nacional - Pereira, Daniel (Africana Studia, 2020)
This article establishes a comparison between a starting point constituted by the extreme low level of social development in which the archipelago of Cape Verde was in when it became independent in 1975, and the assets accomplished during 30 years. Among the explaining factors of this relative success – measure both by the material indicators as well as by the successes of international politics in the regional and international scope - are, besides the traditional strategic advantage of the localization of the islands, the benefits associated to its political stability, unusual in the African context, and the maintenance of a pragmatic diplomacy.